Joaquin Torres Garcia : en la crisis del arte moderno - Fló, Juan, 1930-; Peluffo, Gabriel, 1946- (Montevideo : Estuario, Gabriel, 2021)
It took more than thirty years for these essays of Juan Fló on the work and thought of J.T.G. to be compiled. No one can doubt that he is the leading scholar and greatest scholar on the work of modernist artist Joaquin Torres García. Already since the 50s, after a stay in Europe in which he studied philosophy in France and dedicated a good time to museums, Fló studies the work and thought of J.T.G. in relation to the process of transformation of art and ideas during the 20th century, which has given rise to voluminous works that have remained unpublished and dispersed until now. Even if some of the writings compiled here have obeyed circumstantial demands such as exhibition catalogs, magazines, weeklies, international congresses or agreements concluded with one's own Museo Torres García, in all of them there is an indeclinable intellectual commitment of the author with the subject treated, and if there is reiteration of certain concepts, it takes place in different analytical contexts, so that they always require a new reading and interpretation. "Fló was a frequent assistant of the Torres García Workshop and witness several talks by the noted artist since 1945, through his friendship with Manuel Aguiat." (HKB Translation) --Page 15.
Prólogo / Gabriel Peluffo Linari -- Significación de Torres García -- Joaquín Torres García. Escritos -- En el centenario, Joaquín Torres García: un destino americano -- Torres García en (y desde) Montevideo -- Malos tiempos para Joaquín Torres García -- El Museo Torres García -- Torres García -- Joaquín Torres García: enigmas, equívocos, contradicciones -- Torres García 1915-1922: algunos enigmas -- Torres García: Nueva York -- Notas sobre las pinturas de Nueva York -- Los frescos del Salón de San Jorge -- Joaquín Torres García y el arte prehispánico -- Joaquín Torres García: las ideas.
Includes bibliographical references.
In Spanish.
Keywords: Torres-García, Joaquín, -- 1874-1949 -- Criticism and interpretation; Constructivism (Art) -- Uruguay; Art, Uruguayan -- 20th century